1997
DOI: 10.1093/jn/127.7.1260
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Uptake and Biliary Excretion of the Isoflavone Genistein in Rats , ,

Abstract: The intestinal absorption, biliary excretion and metabolism of genistein, a potent and specific protein tyrosine kinase inhibitor that occurs naturally in soy foods, was examined in anesthetized, adult female rats fitted with indwelling biliary cannulas. 4-14C-Genistein, when infused into the duodenum, was rapidly absorbed from the intestine, taken up by the liver and excreted into the bile as its 7-O-beta-glucuronide conjugate. Cumulative recovery of 14C-radioactivity in the bile over a 4-h period was 70-75% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
199
1
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(216 citation statements)
references
References 35 publications
14
199
1
2
Order By: Relevance
“…When flavonoid metabolites resulting from intestinal conjugation are secreted in the mesenteric vein, a proportion of them are taken up and metabolized by the liver (3,4,26) and then partially secreted in the bile (20,34,44,45). In our experiments, the presence of flavonoids in the bile for all the tested compounds indicated that whatever their origin, flavonoids undergo enterohepatic cycling.…”
Section: Ajp-gastrointest Liver Physiolmentioning
confidence: 54%
See 1 more Smart Citation
“…When flavonoid metabolites resulting from intestinal conjugation are secreted in the mesenteric vein, a proportion of them are taken up and metabolized by the liver (3,4,26) and then partially secreted in the bile (20,34,44,45). In our experiments, the presence of flavonoids in the bile for all the tested compounds indicated that whatever their origin, flavonoids undergo enterohepatic cycling.…”
Section: Ajp-gastrointest Liver Physiolmentioning
confidence: 54%
“…Some of them, such as catechin, are sparingly secreted in the bile (1%), whereas others, like genistein and eriodictyol, are extensively recycled (32 and 23% of the perfused dose, respectively). The importance of the biliary secretion in genistein bioavailability was previously suggested in a study reporting that 70-75% of genistein perfused in the small intestine was recovered in the bile over 4 h of perfusion (34). By contrast, the biliary secretion of quercetin and catechin appears quite limited, indicating that the biliary pathway probably plays a minor role in their elimination.…”
Section: Ajp-gastrointest Liver Physiolmentioning
confidence: 91%
“…When 4-14 Cgenistein is infused into the duodenum of rats, it is rapidly absorbed from the intestine, taken up by the liver and excreted into the bile as its 7-O-β-glucuronide conjugate 46 . Intestinal perfusion studies have indicated that some of the genistein glucuronide produced in the rat small intestine is returned to the lumen [4][5][6] .…”
Section: Effects Of Intestinal Flora On Metabolism Of Isoflavonesmentioning
confidence: 99%
“…In addition, some of the metabolic products of isoflavones, in particular equol, may be transported in blood weakly associated with serum proteins. Equol, and possibly other isoflavones, are secreted by liver into bile and they therefore can cycle as part of the enterohepatic circulation 13,14 . This cycling may occur several times over one or more days and allows a steady-state concentration of these molecules to develop in blood as long as the intake of soy foods continues on a daily basis.…”
mentioning
confidence: 99%